The Latin renovatio of Byzantium the Empire of Constantinople (1204-1228) - Tricht, Filip van (Medieval Mediterranean, 2011)
This book offers a new perspective on the Latin take-over of Byzantine territories after the crusader sack of Constantinople in 1204, arguing that the new rulers very consciously aimed at continuing the Eastern Empire, drawing many Byzantines to their side.